Kolaborasi Pembelajaran dan Pengabdian: Pengenalan Sejarah serta Budaya Palembang melalui Praktik Penerapan Tour Guide - Dwi Hanadya; Rima Febrianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This collaborative activity aims to integrate academic learning and community service through tour guide practices at the Monpera Museum and the Sultan Mahmud Badaruddin II Museum Palembang. Students are directly involved in introducing local history and culture to visitors, while also practicing communication skills and applying contextual English. The activity method includes observation, field practice, and reflection on learning outcomes. The results of the activity indicate that students gain a deeper understanding of local cultural values, increase their confidence in public communication, and develop an appreciative attitude towards Palembang's historical heritage. This activity also shows the effectiveness of the experiential learning and service-learning approach in developing academic competence as well as the social character of students. Thus, the practice of this tour guide can be utilized as a community-based learning model relevant to higher education in the fields of language, culture, and tourism.